123 The Development of a Dietary Preparation Protocol for Optimal Inflammatory Imaging Using 18F-FDG PET. (3rd June 2016) - Wicks, Eleanor; Menezes, Leon; Blanchflower, Shane; Barnes, Anna; Groves, Ashley; Elliott, Perry
Abstract : Background: Positron emission tomography (PET) performed utilising the glucose analogue and radiotracer 18F-FDG (FDG) to detect active inflammation, offers enormous potential for detecting disease presence and activity in myocarditis. However, the clinical utility of PET imaging is limited by the unpredictable nature of physiological FDG uptake within cardiac muscle. Methods to minimise physiological FDG uptake are necessary to depict active inflammation and to avoid avoid false negative and positive findings. Studies have suggested the use of fasting conditions to shift myocardial metabolism to primary free fatty acid (FFA) utilisation for energy and oxygen consumption to suppress physiological FDG uptake by normal myocardium. Specific dietary preparation regimens using a very high-fat content and low-carbohydrate diet prior to scanning have also been proposed, as has the administration of heparin to reduce FDG uptake through the activation of lipoprotein lipase (LPL) and hepatic lipase (HL) which enhances plasma lipolytic activity and leads to preferential free fatty acid consumption. This study was therefore performed to develop an optimal dietary preparation protocol for imaging in PET/CT. We sought to establish whether patient preparation using heparin in addition to a high fat, low carbohydrate diet and prolonged fast prior to scanning ncreases the diagnostic capability of PET scanning in myocarditis. Methods: All patients referred for PET scans for the assessment of myocarditis were enrolled. We prospectively examined three preparation rationales to determine the optimal rationale for minimising physiological FDG-uptake. All subjects underwent strict preparation prior to scanning using one of the following protocols to enable comparison: A 6-hour fast only, no dietary preparation. Dietary preparation for 24 h prior to the scan with a high-fat content, low carbohydrate diet, followed by a prolonged fast for 12 h. Dietary preparation for 24 h prior to the scan with a high-fat content, low carbohydrate diet, followed by a prolonged fast for 12 h and the administration of 50IU/kg of heparin prior to scanning. The imaging findings were analysed by two independent and blinded clinicians. FDG uptake was categorised as none (complete suppression, no uptake = 0), focal (localised uptake, = 1), focal on diffuse (2) and diffuse (poor, failed suppression, = 4). Results: A total of 280 PET scans were performed. 36 patients underwent preparation using a 6-hour fast only, 128 underwent dietary preparation and a 12-hour fast, and 118 underwent dietary preparation followed by a 12-hour fast and the administration of heparin prior to scanning. A 6-hour fast alone was associated with a 44% failure to suppress physiological metabolism – equivalent to almost one in every two scans being suboptimal or un-interpretable. In contrast, restriction of carbohydrate intake with high fat intake alongside a prolonged 12-hour fast was successful in supressing normal myocardial metabolism in 89% of subjects. Similarly, of those who also received heparin, there was a failure to suppress normal myocardial metabolism in 11% of subjects. Conclusion: Strict patient preparation prior to PET scanning is key to ensuring an optimal diagnostic disease assessment in myocarditis. A short duration of fasting of 6-hours or less alone is suboptimal in suppressing physiological uptake. In contrast, strict dietary preparation (using a high fat, low carbohydrate diet) and prolonged fast of > 12 h increases the diagnostic capability by 75%. Interestingly, the addition of heparin to this regimen provided no additive benefit suggesting that the addition of heparin adds little to the diagnostic quality of scans and is therefore unnecessary.